2015
DOI: 10.1007/s10551-015-2827-6
|View full text |Cite
|
Sign up to set email alerts
|

How Servant Leadership Influences Organizational Citizenship Behavior: The Roles of LMX, Empowerment, and Proactive Personality

Abstract: While the link between servant leadership and organizational citizenship behavior (OCB) has been established, the individual-level mechanisms underlying this relationship and its boundary conditions remain poorly understood. In this study, we investigate the salience of the mediating mechanisms of leader-member exchange (LMX) and psychological empowerment in explaining the process by which servant leaders elicit discretionary OCB among followers. We also examine the role of followers' proactive personality in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
366
2
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 393 publications
(407 citation statements)
references
References 79 publications
23
366
2
16
Order By: Relevance
“…An example item is "my supervisor gives encouragement and recognition to staff". LMX quality was measured using the seven-item measure (LMX7) developed by Graen and Uhl-Bien (1995) that has been used in the Chinese context before (e.g., Newman et al 2015) (α = .79). An example item is "My supervisor recognizes my potential".…”
Section: Control Variablesmentioning
confidence: 99%
“…An example item is "my supervisor gives encouragement and recognition to staff". LMX quality was measured using the seven-item measure (LMX7) developed by Graen and Uhl-Bien (1995) that has been used in the Chinese context before (e.g., Newman et al 2015) (α = .79). An example item is "My supervisor recognizes my potential".…”
Section: Control Variablesmentioning
confidence: 99%
“…Five studies showed a positive relationship between servant leadership and organisational citizenship behaviour [6,7,[75][76][77]. One study reported a positive relationship between servant leadership and service-orientated organizational citizenship behaviour, mediated by leader-member exchange [78].…”
Section: Individual Outcomesmentioning
confidence: 99%
“…Positive psychological capital mediated the relationship between these two variables. Other factors that mediated the relationship between servant leadership and organisational citizenship behaviour were leader-member exchange [75], psychological contract [76], commitment to supervisor, self-efficacy, procedural justice climate, and service climate [77].…”
Section: Individual Outcomesmentioning
confidence: 99%
“…Although, there is no overall consensus about the exact behavior of the servant leader, but most of the studies followed the definition of Greenleaf (1977), that defined servant leadership as the one who emphases on empowering and development of followers, while at the same time inspires the followers to act as servant leaders too (Newman, Schwarz, Cooper, & Sendjaya, 2015). Ehrhart (2004) highlighted seven main characteristics of servant leadership: putting followers first, support followers to develop and success, build relations with followers, empowered them, having conceptual skills, behave ethically, and create value for the community.…”
Section: Servant Leadershipmentioning
confidence: 99%